Sermons for the Liturgical Year - Feiss, Hugh (Brepols, 2018)
The Canons Regular who followed the Rule of St Augustine at St Victor of Paris in the twelfth century bequeathed to subsequent generations a legacy of over 200 carefully crafted sermons for the major feasts of their liturgical year. The sermons that Maurice de Sully, bishop of Paris (1160-1196) prepared in Latin and Old French for parish priests drew on the expertise of Richard of St Victor. In this volume are sermons by Hugh, Achard, Richard, Walter, and Godfrey of St Victor, Maurice de Sully, and Absalom of Springiersbach, arranged in liturgical order. Most of these sermon appear in English for the first time.